Impacts of Implemented Curriculum on Civic Engagement: Clue as Questionnaire Survey Applying ICCS Framework for Junior High School Students - HORII, Junpei; OGURI, Yuki (Journal of Japanese Educatinal Research Associaon for the Social Studies, 2021)
This study aims to elucidate the impact of implemented curriculum on civic engagement (attained curriculum) of junior high school students and subsequently, examine the conditions for civic engagement learning proposed in social studies educational research, critically. Questionnaires using the ICCS (International Civic and Citizenship education Survey) framework were completed by 1495 junior high school students. Factor analysis was conducted post survey and the results of path analyses indicate that learning from each other in school and learning about school management and school issues have a positive influence on behavioral, emotional, and cognitive engagement of the students. However, only emotional engagement is positively influenced by learning about social issues. This research offers the following considerations:　　First, focusing on school management and school issues was more effective in structured curricula than focusing on the social issues and social relations prerequisites for civic engagement learning. Second, including civic engagement learning only in social studies was ineffective and that engagement in this learning should be included in social studies and other subjects.　　The conclusion also suggests that the limitations of the framework for discussion of social studies education, and proposed a new way of formulating research questions with a set of methodologies.